Sistem Pemantauan Keluaran Generator Set Berbasis IoT - Mudia, Halim; Nofrianto, Aldo; Audy, Audy (Jurnal Pustaka AI (Pusat Akses Kajian Teknologi Artificial Intelligence), 2025)
This research is motivated by the ineffective maintenance of generator sets in hospitals. Gensets are crucial components that serve as backup power sources, especially during power outages from the main grid (PLN). However, in practice, genset maintenance is typically carried out only once every six months. During this time, there are no regular inspections, which means any potential damage or malfunction that occurs before the scheduled maintenance may go unnoticed. This can lead to operational disruptions in hospital areas that heavily rely on a stable power supply, like ICUs, operating rooms, and laboratories. A more effective and real-time genset monitoring system is required. This research aims to develop an Internet of Things (IoT) based genset condition monitoring system that can monitor key output parameters of the genset in real time. The monitored parameters include voltage (phases R, phases S, and phases T), current (phases R, phases S, and phases T), frequency, power (phases R, phases S, and phases T), total power, and generated energy. The data will be automatically transmitted to the Ubidots platform via the internet, allowing users to monitor the genset's condition anytime and anywhere through the website. This system is expected to improve maintenance effectiveness and minimize the risk of equipment failure.